LOYALTY, QUALITY OF WORK LIFE, ORGANIZATIONAL CULTURE, AND WORK MOTIVATION CREATING ORGANIZATIONAL CITIZENSHIP BEHAVIOR (Study at North Penajem Paser District Health Office) - Syarifah Asmawati; Farida Yuliaty; Etty Sofia (Jurnal Scientia, 2023)
Organizations, both profit-oriented and non-profit organizations, expect the maximum possible performance from their employees to achieve the goals set. The North Penajam Paser District Health Office is a local government organization that provides health services to the community. Health services provided must certainly be able to provide satisfaction to the community it serves. Human resources who perform excessively compared to what has been set are termed Organizational Citizenship Behavior (OCB). The purpose of this study was to examine and analyze the influence of loyalty, quality of work life , organizational culture and work motivation on OCB either partially or simultaneously. This study has five variables consisting of one dependent variable and four independent variables. Organizational Citizenship Behavior (OCB) as the dependent variable (Y), Loyalty (X1), Quality of Work Life (X2) , Organizational Culture (X4), and Work Motivation (X5) as independent variables. Respondents in this study were employees at the North Penajam Paser District Health Office. The number of samples in this study were 84 people, the analytical tool used was multiple linear regression. The results showed Loyalty, Quality of Work Life , Organizational Culture, and Work Motivation have a simultaneous influence on OCB. Partially Loyalty has a significant influence on OCB, as well as Organizational Culture and Work Motivation have an influence on OCB. However, the Quality of Work Life variable has no effect on OCB.